With the Help of One's Neighbors : Externalities in the Production of Nutrition in Peru - Alderman, Harold; Hentschel, Jesko; Sabates, Ricardo (World Bank, Washington, DC, 2014)
Both public, and private resources contribute to children's nutritional status. And investments by one household may improve health in other neighborhood households, by improving the sanitation environment, and increasing shared knowledge. The authors measure the externalities of investments in nutrition, by indicating the impact of women's education in Peruvian neighborhoods, on children's nutrition in other households, after controlling for those households' education, and income. They find that in rural areas this shared knowledge has a significant impact on nutrition. The coefficient of an increase in the average education in the neighborhood is appreciably larger than the coefficient of education in isolation. That is, educating women in rural areas, improves all children's nutritional status, even for those whose caregivers are themselves not educated. In both urban, and rural areas, they observe externalities from investments in sanitation made by neighboring households. They do not find the same externalities in the case of investments, only in the household water supply. There is a direct link between the caregivers' education, and their children's health status. Education transmits information about health, and nutrition. It teaches numeracy, and literacy, which help caregivers read labels, and instructions. Bu exposing caregivers to new environments, it makes them receptive to modern medical treatment. It gives women the confidence to participate in decision-making within a household, and it gives men, and women the confidence to interact with health care professionals.